Molecular Docking Investigation of Caffeic Acid Phenethyl Ester (CAPE) Interaction with IL-6 and TNF-α for Anti-Inflammatory Potential - Aisyah Nabila; Khalish Arsy Al Khairy Siregar; Paula Mariana Kustiawan (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Inflammation is a physiological response to tissue injury mediated by pro-inflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Although conventional anti-inflammatory drugs are effective, their long-term use is associated with adverse effects, prompting interest in safer natural alternatives. Caffeic acid phenethyl ester (CAPE), a major bioactive constituent of propolis, has been reported to exhibit anti-inflammatory properties. This study aimed to investigate the interaction of CAPE with IL-6 and TNF-α using molecular docking to evaluate binding affinity and molecular interactions. Docking simulations were performed to predict the binding behavior of CAPE and compare it with diclofenac sodium as a reference compound. CAPE exhibited binding affinities of −5.1 kcal/mol against TNF-α and −5.0 kcal/mol against IL-6, whereas diclofenac sodium showed slightly stronger binding affinities of −5.5 kcal/mol and −5.2 kcal/mol, respectively. In addition, CAPE shared several interacting residues with the reference compound, suggesting a similar binding orientation within the active sites of both proteins. These findings indicate that CAPE possesses favorable binding characteristics toward TNF-α and IL-6. However, the obtained binding affinities represent preliminary predictions of ligand–protein interactions and require further validation through molecular dynamics simulations and experimental studies. This study provides molecular insights into the anti-inflammatory potential of propolis-derived compounds and supports their further exploration as natural lead compounds for anti-inflammatory drug development.